Conceptualization Of The Islamic Quality Management Model For Non-Profit Islamic Based Development Institutions In Malaysia - Mokhtar, Mohd Sadiq Mohd (2023)
Non-Profit Islamic Based Development Institution (NPIBDI) has been an essential institution for Muslims. Malaysia is Muslim majority country with Islam as the religion of the Federation. To the Islamic world, Malaysia is the role model in terms of its Islamic institutions. However, past researchers raised issues regarding NPIBDI in Malaysia, which is found to be underachieved compared to profit-based Islamic institutions as the level of confidence to these institutions are low. Even though NPIBDI is a non-profit entity, NPIBDI manage a considerable amount of funds and is susceptible to mismanagement. Therefore, past researchers suggested that the NPIBDI implement a conventional quality management model. However, arguments by researchers show that these quality management models are unsuitable to be implemented in Islamic institutions based on the Islamic philosophical perspectives. On the other hand, Malaysia introduced shariah based Islamic Quality Management (MS1900), whose aim is to fill the gap left by conventional quality management. However, past researchers also criticised MS1900 because some of the concepts are still within the conventional quality management paradigm, which does not align with the Islamic philosophical paradigm.